Inference about a Binomial Proportion under Privacy Protection (International Journal of Statistical Sciences, 2026)
In this paper we consider the inferential problem for a Binomial proportion in situations when the exact number of units possessing an attribute under consideration is unavailable due to privacy reasons; however a synthesized version of this number is available. The inference problem is addressed under three types of available information: noise added version and plug-in sampling based and posterior sampling based data. A comparison of the three modes of data source is made based on inferential accuracy and a measure of privacy.IJSS, Vol. 26(1), March, 2026, pp 65-82